Flexural behaviour of bamboo-based bamboo cement slab panels with GGBFS (Ground Granulated Blast Furnace Slag) - Hylga Rohman; Murni Dewi, Sri; Susanti, Lilya (Rekayasa Sipil, 2025)
Recently, in response to the problem of global warming and the need for a sustainable society, production using natural materials has begun to increase. Bamboo, which is low in price, fast-growing, and widespread, is believed to contribute greatly to construction. Bamboo, available in abundance, can be used as a substitute for iron or wire. GGBFS, a residue from steelmaking, can be used as a substitute for cement in standard mortar or concrete mixes. The flexural properties of ferrocement slab panels using bamboo have been analyzed to increase the service capacity limit. Experimental studies were conducted on supported ferrocement slab panels with gradually increasing loads. The series of experiments involved testing 12 ferrocement slab panels of size 300 mm x 600 mm and thickness 50 mm. From these plates, 4 test samples were made using a conventional mortar mix of 1:2 and variations of 0%, 10%, 20%, and 30% cement replacement. Bamboo strips were used as structural reinforcement. The samples were poured, stored in moist gunny sacks for 28 days, and then tested with a three-point load. The test results were then compared with the theoretically expected results. The evaluation results showed that the initial cracking load and experimental failure load occurred at the center of the slab in all four types of slabs. The maximum load is about twice the initial cracking load. Each of the plates showed significant flexibility before reaching ultimate failure. In this case, cement bamboo slabs can be used for roofs or structures that do not require high loads.